Model Pembelajaran Cooperative Learning Tipe TGT dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran SKI di MA Darut Taqwa Pasuruan - Radinda Aurellia Ramadhani (CV. ITTC INDONESIA, 2025)
This study aims to describe how the implementation of the Teams Games Tournament (TGT) Cooperative Learning model improves students' learning motivation in the Islamic Cultural History subject at MA Darut Taqwa. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results show that the implementation of the TGT learning model is able to create an active, competitive, and enjoyable learning atmosphere. Students are more motivated to participate in learning, show increased enthusiasm, and are able to work well in teams. Therefore, this model is recommended as an alternative strategy in improving students' learning motivation, especially in IS subjects.